Management of bridges Anglo-French liaison report = Gestion des ponts : Rapport conjoint franco-britannique (Thomas Telford, 2005)
Describing the bridge stocks in France and the UK, this book gives an overview of the organisational structures for the management of bridges. It also compares procedures for inspection, assessment and maintenance planning. It is an outcome of the joint venture between France and the UK to review procedures for the management of highway bridges.